Eriophyoid mites from Hainan Province, China III: Descriptions of three new genera and three new species of Colomerini (Acari: Eriophyoidea) - Xue, Xiao-Feng; Cheng, Li-Sheng; Hong, Xiao-Yue (Zootaxa, 2011)
Three new genera and three new species in the tribe Colomerini of the Eriophyidae (Acari: Eriophyoidea) from China’s Hainan Island are described and illustrated. They are Paraisoannulus machiles gen. nov. and sp. nov. on Machilus gamblei King ex Hook. f. (Lauraceae), Pentacecidophyes xinglongis gen. nov. and sp. nov. on Litchi chinensis Sonn. (Sapindaceae) and Paracaridilophus retusus gen. nov. and sp. nov. on Fissistigma retusum (Lévl.) Rehd. (Annonaceae). All the new species described herein are vagrants on their respective host plant.